Pengembangan model literasi politik generasi Z pada pemilihan umum 2024 di MAN 1 Bojonegoro - Septian, Esa; Wulandari, Septi; Ratih, Peppy Nala; Darmawan, Kidung Bukit (STAI Auliaurrasyidin Tembilahan, 2024)
Generation Z is a development milestone in determining the next leader. This community service aims to support the existence of young people who can use social media as a place to improve political literacy. This activity is carried out to provide knowledge transfer and is expected to be able to encourage students as novice voters to actively participate in the 2024 general election so that it can be held with integrity and quality. MAN 1 Bojonegoro is the target of this socialisation because class XII students as novice voters still lack political literacy. This is when students have the provision to make choices that are not easily consumed by political issues and harmful disinformation. The social media smart movement is a place to increase the role of participating in political literacy as citizens who uphold democracy.